1999
DOI: 10.1044/jslhr.4203.690
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Generalization of Complex Sentence Production in Agrammatism

Abstract: The present study applies single-subject experimental design to examine (a) the acquisition and generalization of complex sentence production in agrammatism using Linguistic Specific Treatment (LST) and (b) the utility of syntactic theory in guiding hypotheses of treatment effects. LST trains construction and production of complex sentence structures. Four sentence types were selected for study: object clefts and object-extracted matrix and embedded questions (which are noncanonical with wh-movement), and embe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
87
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 21 publications
13
87
1
Order By: Relevance
“…While many patients are able to acquire a targeted skill in a structured format, many patients do not successfully use the trained skill in more functional situations (Ballard & Tompson, 1999;Coelho, 1990; Purdy, Duffy & Coelho, 1994;Robson, Pring, Marshall, Morrison, & Chiat, 1998;Rostron, Ward & Plant, 1996; Yoshihata and colleagues, 1998). Purdy, Duffy, and Coelho (1994) performed a study examining use of symbols trained in verbal, gestural, and communication board modes.…”
mentioning
confidence: 99%
“…While many patients are able to acquire a targeted skill in a structured format, many patients do not successfully use the trained skill in more functional situations (Ballard & Tompson, 1999;Coelho, 1990; Purdy, Duffy & Coelho, 1994;Robson, Pring, Marshall, Morrison, & Chiat, 1998;Rostron, Ward & Plant, 1996; Yoshihata and colleagues, 1998). Purdy, Duffy, and Coelho (1994) performed a study examining use of symbols trained in verbal, gestural, and communication board modes.…”
mentioning
confidence: 99%
“…The treatment approach also might result in markedly different outcomes. Thompson and colleagues have shown, for example, that linguistic specific treatment of sentence production deficits in agrammatic aphasia results in generalization to untrained sentences that are linguistically similar to those trained, indicating improved access to the structures and computations required to produce sentences (Ballard & Thompson, 1999;Thompson & Shapiro, 1995;Thompson et al, 1998). Conversely, treatment aimed at teaching certain functional behavior results in increased use of trained responses, but little generalization to untrained responses (Thompson 1989).…”
mentioning
confidence: 99%
“…In particular, as noted in the introduction, studies of the TUF approach (Ballard & Thompson, 1999;Jacobs & Thompson, 2000;Thompson & Shapiro, 2005;Thompson et al, 1993Thompson et al, , 1996Thompson et al, , 1997 frequently observed greater generalization to sentences with the same type of movement than to sentences with a different type of movement. Furthermore, it is important to highlight that the focus of the treatments in the current study was on the identification of thematic role in comprehension, which addresses movement only implicitly.…”
Section: Discussionmentioning
confidence: 99%
“…One of the goals of TUF is to promote generalization from trained to untrained sentences; therefore, researchers systematically probe progress on syntactically related and unrelated untrained sentence structures. It has been found that generalization following TUF is greatest to linguistically related sentences (Ballard & Thompson, 1999;Jacobs & Thompson, 2000;Thompson & Shapiro, 2005;Thompson, Shapiro, & Roberts, 1993;Thompson, Shapiro, Tait, Jacobs, & Schneider, 1996;Thompson et al, 1997), lending support for specific deficit hypotheses that suggest that specific syntactic operations lie at the root of deficits. Furthermore, generalization occurs frequently from complex to simple structures but less frequently from simple to complex structures (Thompson, Ballard, & Shapiro, 1998;Thompson & Shapiro, 2005Thompson, Shapiro, Kiran, & Sobecks, 2003;Thompson et al, 1993Thompson et al, , 1997.…”
mentioning
confidence: 86%
See 1 more Smart Citation